(untitled) (مجلة المنصور, 2022)
There is no doubt that Anesthetics crime is one of the sociality crimes which to hinder development of humanity and economic in societies ,and crime passing for international borders , therefore necessitate for search in rooting it legal in Iraqi legislation study treatment it as legal in other states and this which I adoption it in my studying these and we chose number deferent countries in the world for be first new studying for merge with comparison the judgments nationally criminal in Iraq and in other states concerning struggle and anesthetics Incrimination and crimes which contain it under framework it the criminal and clarification corner it as felony and penalties it according to lawful rules which were mentioned in patriotism laws as penalties law of the Iraqi to number 111 for year 1969 and other laws and decisions which issued for anesthetics Incrimination, I talked first briefly about the definitions concerning with mention to point of view of Islamic sharia of it, Through the research we studied this crimes in describing and analyzing it comparing with deferent laws. for knowledge of concepts that crimes I was mentioned some of conclusions taken from by our search text crowned it by mention a number of the recommendations and suggestions which I see it necessary for struggle and limitation of anesthetics crimes growth in our country Iraq